2009
DOI: 10.1007/s11250-009-9355-2
|View full text |Cite
|
Sign up to set email alerts
|

Huizache (Acacia farnesiana) whole pods (flesh and seeds) as an alternative feed for sheep in Mexico

Abstract: Two experiments were undertaken to evaluate the use of pods from Huizache (Acacia farnesiana), common in the arid and semiarid regions of Mexico, on the perfromance and apparent digestibility in Pelibuey Mexican hair growing ewe lambs. Twenty-four Pelibuey ewe lambs were used in the animal performance experiment, with a mean live weight of 14.91 +/- 1.48 kg, randomnly allocated to three groups which received ad libitum for 77 days (11 weeks) experimental whole rations T0 with 0%, T12 with 12% or T24 with 24% i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 13 publications
2
13
0
1
Order By: Relevance
“…Results on composition indicated that the shrubland species are characterized by high fibre contents and poor protein values; these results are in line with other vegetation assessments from low precipitation areas (Baraza et al, 2008;García-Winder et al, 2009). Although Acacia, Mimosa, Prosopis and Verbasina species had high crude protein contents, the use of some of these resources might be limited due to the presence of large tannin contents, which are a part of PBC (Ben Salem et al, 2005;Jiménez-Ferrer et al, 2008).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Results on composition indicated that the shrubland species are characterized by high fibre contents and poor protein values; these results are in line with other vegetation assessments from low precipitation areas (Baraza et al, 2008;García-Winder et al, 2009). Although Acacia, Mimosa, Prosopis and Verbasina species had high crude protein contents, the use of some of these resources might be limited due to the presence of large tannin contents, which are a part of PBC (Ben Salem et al, 2005;Jiménez-Ferrer et al, 2008).…”
Section: Discussionsupporting
confidence: 88%
“…The CP values of the Opuntia species in our study were around the 6% previously reported (Baraza et al, 2008;Parveen et al, 2010). Despite the good CP results of some of the shrub species, their exclusive use for goat feeding could cause temporary nutritional imbalances or permanent undernourishment, especially during dry seasons when grazing pressure is higher and the availability and nutritive value of forages decreases dramatically (García-Winder et al, 2009). To cope with this risk, proper supplementation during dry seasons is highly recommended (Galina et al, 2007).…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…However, much of the goat milk production system in Mexico has historically been based on extensive systems, where animals roam the local rangeland for food, with different seasonal availability (6), which can affect the quality of the milk since fodder quality apparently is the most important factor (7). It is generally accepted that of the 2 common production systems, extensive and intensive feeding systems, the former pasture-based system has been found to provide healthier compounds in milk (8).…”
Section: Introductionmentioning
confidence: 99%